A Flexible Si@C Electrode with Excellent Stability Employing an MXene as a Multifunctional Binder for Lithium‐Ion Batteries. Issue 6 (13th August 2019) - Zhang, Peng; Zhu, Qizhen; Guan, Zhaoruxin; Zhao, Qian; Sun, Ning; Xu, Bin
Abstract: Silicon is a promising anode material with high capacity for lithium‐ion batteries (LIBs) but suffers from poor conductivity and large volume change during charge/discharge. Herein, by using two‐dimensional conductive MXene as a multifunctional binder instead of conventional insulating polymer binders such as poly(vinylidene fluoride) or carboxymethylcellulose sodium (PVDF and CMC, respectively), a free‐standing, flexible Si@C film was fabricated by simple vacuum filtration and directly used as anode for LIBs. In the MXene‐bonded Si@C film, MXene constructed a three‐dimensional conductive framework in which Si@C nanocomposites were embedded. Its loose and porous structure provided much space to buffer the large volume expansion of Si@C nanoparticles and thus led to significantly superior cycle stability compared with conventional CMC‐ and PVDF‐bonded Si@C electrodes. Moreover, the porous structure and the metallically conductive MXene offered fast ion transport and outstanding conductivity of the MXene‐bonded Si@C film, which were favorable for its rate performance. These results promise good potential of the MXene‐bonded Si@C film electrode for LIBs. Abstract : MXene can do it better : A flexible Si@C film electrode for lithium‐ion batteries is fabricated by using an MXene as a multifunctional binder. The MXene simultaneously acts as a binder, a flexible framework, a conductive additive, and a buffer for the large volume change of Si@C during the charge/discharge process, and it thus results in superior cycling stability and rate performance.